Weaving culture: The many dimensions of the Yup’ik Eskimo mingqaaq - Lee, Molly (Études/Inuit/Studies, 2004)
AbstractAs a general rule, so-called tourist arts are thought of as greatly simplified and less closely tied to the indigenous cultures that make “traditional” art forms. In this article, I argue that the Yup’ik Eskimo coiled basket (mingqaaq), an art form developed specifically for sale to outsiders, is in fact closely connected to modern Yup’ik culture through its use of raw materials (beach, or rye grass and sea-mammal intestine). Its recent appearance around Alaska in various media—on a telephone book cover, in a logo for a Native Corporation, and as a stage prop on the podium beside a Native leader arguing the subsistence cause, to name a few—suggests that the mingqaaq, the most widely sold Yup’ik art form today, may have taken on the role of political symbol for the highly contentious issue of Alaska Native subsistence rights.